Reconnection events in Saturn's magnetotail: Dependence of plasmoid occurrence on planetary period oscillation phase. Issue 4 (6th April 2016) - Jackman, C. M.; Provan, G.; Cowley, S. W. H.
Abstract: During its exploration of Saturn's magnetotail the Cassini magnetometer has detected many in situ examples of magnetic reconnection, in the form of plasmoids, traveling compression regions (TCRs), and dipolarizations. Meanwhile, many magnetospheric phenomena have been shown to be organized with particular regularity by planetary period oscillation systems driven separately from the Northern and Southern Hemispheres of the planet. Here we examine the relationship between the occurrence of plasmoids and TCRs and the magnetic phases of the northern and southern systems. We find a striking degree of organization of the events by both northern and southern phases, with events linked preferentially to intervals in which the magnetospheric plasma and field lines are displaced outward from the planet and the current sheet thinned, both effects being likely to favor the occurrence of reconnection and plasmoid‐related mass loss. Little evidence is found for significant visibility effects associated with north‐south motions of the plasma sheet. Key Points: Tail reconnection at Saturn organized by northern/southern phase Events linked to current sheet thinning and outward displacement of field and plasma Little evidence for visibility effects associated with north‐south motions of the plasma sheet